Crucial Role of Extracellular Polysaccharides in Desiccation and Freezing Tolerance in the Terrestrial Cyanobacterium Nostoc commune - Tamaru, Yoshiyuki (American Society for Microbiology, 2005)
The cyanobacterium Nostoc commune is adapted to the terrestrial environment and has a cosmopolitan distribution. In this study, the role of extracellular polysaccharides (EPS) in the desiccation tolerance of photosynthesis in N. commune was examined. Although photosynthetic O(2) evolution was not detected in desiccated colonies, the ability of the cells to evolve O(2) rapidly recovered after rehydration. The air-dried colonies contained approximately 10% (wt/wt) water, and field-isolated, natural colonies with EPS were highly water absorbent and were rapidly hydrated by atmospheric moisture. The cells embedded in EPS in Nostoc colonies were highly desiccation tolerant, and O(2) evolution was not damaged by air drying. Although N. commune was determined to be a mesophilic cyanobacterium, the cells with EPS were heat tolerant in a desiccated state. EPS could be removed from cells by homogenizing colonies with a blender and filtering with coarse filter paper. This treatment to remove EPS did not damage Nostoc cells or their ability to evolve O(2), but O(2) evolution was significantly damaged by desiccation treatment of the EPS-depleted cells. Similar to the EPS-depleted cells, the laboratory culture strain KU002 had only small amount of EPS and was highly sensitive to desiccation. In the EPS-depleted cells, O(2) evolution was also sensitive to freeze-thaw treatment. These results strongly suggest that EPS of N. commune is crucial for the stress tolerance of photosynthesis during desiccation and during freezing and thawing.